2017
DOI: 10.1136/jnnp-2017-316946
|View full text |Cite
|
Sign up to set email alerts
|

Approaches to neuromodulation for schizophrenia

Abstract: Based on the success of deep brain stimulation (DBS) for treating movement disorders, there is growing interest in using DBS to treat schizophrenia (SZ). we review the unmet needs of patients with SZ and the scientific rationale behind the DBS targets proposed in the literature in order to guide future development of DBS to treat this vulnerable patient population. SZ remains a devastating disorder despite treatment. Relapse, untreated psychosis, intolerable side effects and the lack of effective treatment for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(32 citation statements)
references
References 88 publications
0
31
0
1
Order By: Relevance
“…12 Studies have also reported its benefit in reducing recurrence rates, decreasing the intensity of residual psychosis, and improving cognitive impairment by reducing the negative symptoms. 3 Results from the Corripio et al 25 case report revealed the great potential of this procedure, with a significant improvement in symptoms and only one side effect, which was reversible. 25 However, one disadvantage is the fact that it is still an invasive procedure that has the risk of causing edema, hemorrhages, and seizures.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…12 Studies have also reported its benefit in reducing recurrence rates, decreasing the intensity of residual psychosis, and improving cognitive impairment by reducing the negative symptoms. 3 Results from the Corripio et al 25 case report revealed the great potential of this procedure, with a significant improvement in symptoms and only one side effect, which was reversible. 25 However, one disadvantage is the fact that it is still an invasive procedure that has the risk of causing edema, hemorrhages, and seizures.…”
Section: Discussionmentioning
confidence: 95%
“…Studies have shown that its hyperactivation would be the cause of the hyperdopaminergic state, since its activation stimulates GABAergic neurons in the NAcc, which, in turn, inhibits the GABAergic neurons of the globus pallidus (GP), which are responsible for the inhibition of the dopaminergic neurons in the VTA. 3,[11][12][13] In contrast, a hypodopaminergic state in the mesocortical circuit, linking the VTA to the PFC, would be related to negative symptoms. 1,2 According to the GABAergic and glutamatergic hypotheses, an imbalance in the dopaminergic pathways is related to changes in regulation caused by gamma-aminobutyric acid (GABA) and glutamate.…”
Section: Circuitrymentioning
confidence: 99%
See 2 more Smart Citations
“…There is current interest in targeting several important network hubs using DBS in ultra-resistant schizophrenia involved in basal ganglia-thalamocortical and DLPFC brain circuits. Hubs identified include the hippocampus, ventral and associated striatum, medial and DLPFC, substantia nigra, nucleus accumbens and the mediodorsal nucleus of the thalamus ( 203 205 ). These hubs have been chosen primarily based on known pathological findings in schizophrenia and/or their interconnectedness to other brain hubs that are circuit-specific and related to the excessive and mistimed dopamine release in the striatum.…”
Section: Circuit-based Neurosurgerymentioning
confidence: 99%